Entrepreneurship amongst Somali migrants in South Africa - Ibrahim, Bashir Sheikh (My University, 2016)
This study focused on understanding the drivers of entrepreneurship amongst Somali migrants in South Africa. An administered survey questionnaire and in-depth case studies are used to explore the manner in which Somalia migrants, who arrive in South Africa, as refugees, establish enterprises and thrive in the business environment despite their uncertain status and limited access to investment capital or other supportive initiatives. Drawing on the wider available literature a broad conceptual framework was used to guide and shape the areas of detailed exploration. These broadly include, a) the socio cultural explanations, b) the push and pull factors that encourage entrepreneurial activities, and c) the environmental factors (economic and legal) that facilitate entrepreneurship amongst migrants. At an overall level, there are no ‘secret’ transferable ingredients for such entrepreneurship. The study reveals that it is a combination of historic factors and elements of ‘social capital’ that shape and motivate entrepreneurship activities amongst these migrants. The lessons derived can and are being be used to inform policy interventions to shape entrepreneurship in the wider society. However, there has to be appreciation of the unique circumstances and historic incentive opportunities that drive particular practices. In so doing, the study concluded on the need for further research in this terrain and the importance of building a deeper understanding on verifiable and substantive quantitative and qualitative data. Keywords: Migrant Entrepreneurship, Social Capital, Small Enterprises, Somali Refugees, South Africa
A research report submitted to the Faculty of Management, University of the Witwatersrand, in 50 per cent fulfilment of the requirements for the degree of Master of Management (in the field of Public and Development Management). February, 2016
Keywords: Refugees--Somalia; Immigrants--South Africa; Entrepreneurship--South Africa